PEMBERDAYAAN MASYARAKAT DESA SULING KULON, BONDOWOSO MELALUI PEMBUATAN PUPUK ORGANIK DARI LIMBAH PETERNAKAN SAPI UNTUK MENDUKUNG PERTANIAN BERKELANJUTAN - Ramadhani, Debi Sekar; Inayati, Alvi Nur; Sundahri, Sundahri; Ghifari, Chubab ‘Ainul Yaqin al; Prasetya, Ghifarizky Zannu; Asyraf, Mutiara Rafsya; Salsabilla, Aurelia Nur; Sinaga, Haryati Eirene; Bahreisy, Salman; Kondi, Rindu Anjasmoro; Daniar, Resa Dyna (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2024)
Suling Kulon Village has abundant natural resources, the majority of the people of Suling Kulon Village work as farmers and ranchers. Almost every house in Suling Kulon Village keeps cattle. However, the community still does not have awareness of environmental hygiene by allowing cow dung to accumulate in one place without further processing. Cow dung can be used as organic fertilizer which will later be useful for local agriculture, by changing organic fertilizer farmers can overcome the problem of increasingly expensive chemical fertilizers. Cow manure used as organic fertilizer contains macro and micro nutrients which are very useful for plant growth and development and the use of organic fertilizers does not contain chemical elements so that it has no residue. By using organic fertilizers, the soil will be healthier and more fertile. From the existing problems, KKN students have a solution by holding socialization work programs and training in making organic fertilizers so that people are aware of a healthy environment, know how to make organic fertilizers and can implement them at home. This community service activities had been carried out for 45 days from 12th of July to 21st of August 2023. Making organic fertilizer made from cow dung can certainly be an alternative for restoring soil conditions. Organic fertilizer could help fertilize the soil and make agricultural land use sustainable. Apart from that, the manufacture of organic fertilizer made from cow dung also provides benefits for farmers and the community. One of them was in the economic sector, cattle breeders can make a profit by selling the results of making organic fertilizer.